Strategi Komunikasi Dinas Lingkungan Hidup Pelalawan Dalam Pengendalian Pencemaran Udara Industri di Pangkalan Kerinci Kota Kabupaten Pelalawan - Reza Argianto; Yasir Yasir (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Pangkalan Kerinci is an area with many industries in it, including the pulp industry or paper pulp producer. PT RAPP is a company operating in the pulp sector. As a result of this industry, many people complain about air pollution due to industrial activities carried out by PT. RAPP. These activities are monitored by the Pelalawan Regency Environmental Service in collaboration with other stakeholders. The aim of this research is to find out how the planning, implementation and evaluation of communication from the Pelalawan Regency Environmental Service is in controlling industrial air pollution in Pangkalan Kerinci City, Pelalawan Regency. This research is a type of qualitative research with descriptive methods. The subject in this research is the Pelalawan Regency government (Environmental Service) with the determination using purposive techniques. Data collection techniques in this research are through interviews, observation and documentation. The number of informants in the study was 9 people according to the criteria determined through purposive sampling. The data analysis technique used uses the model from Miles and Hubberman and the data validity technique, namely triangulation. The result of this research is that the planning carried out by the Pelalawan Regency Environmental Service was carried out by listening to complaints from the surrounding community, always formulating objectives to provide understanding to the community and then develop message by conveying environmental messages in an informative, persuasive and cognitive manner, which is then continued with media production planning by the Pelalawan City environmental service. The Environmental Service carried out planning implementation after presenting the work program idea, then carrying out technical guidance outreach activities related to PP Number 22 of 2021, collaborating with NGOs and local communities and conveying environmental messages through billboards. Meanwhile, evaluation activities are carried out every six months.